Simulações por CFD da fluidodinâmica em cabine aerosol box para diferentes condições operacionais - Fanticelli, Giulianno Andrade (Universidade Federal de São Carlos, 2021)
During the treatment of diseases that causes respiratory issues, such as Covid-19, patients sometimes require endotracheal intubation procedures in which healthcare workers are highly exposed to viral agents that are dispersed through the air via respiratory particles. One of the protective devices that can be used to mitigate the risk of infection is the aerosol box, a cabin that provides an additional physical barrier to protect the health care worker during endotracheal intubation, reducing his/her exposure to infectious aerosols. The equipment can be used with different configurations, such as the number of entrances for health care workers’ arms, openings for air intake, number of fans that perform aspiration of air on top of the cabin, among others. Therefore, this graduation study aimed to analyze by Computational Fluid Dynamics (CFD) different operating conditions of an aerosol box and choose the best option among the simulated ones, seeking to indicate better conditions of particles removal and air circulation in the cabin. Using CFD with Ansys Student R2 2020 software, 6 cases were simulated with different cabin and particle injection configurations, varying operating conditions such as quantity of aspirators, air suction flow rate in the aspirators and breathing particle velocities. After the simulations, the results were discussed in terms of air velocity contours, particle distribution and particle removal efficiency in the cabins for each case. According to the changes in particle velocity parameters and number of fans, it was concluded that the highest particle removal efficiencies were observed in the cases with only 1 fan, highlighting the case with the lowest particle velocity.
CFD simulations of the fluid dynamics in an aerosol box for different operating conditions
Keywords: CFD; Aerosol box.; Fluidodinâmica computacional; Computational fluid dynamics; CFD; Aerosol box; ENGENHARIAS::ENGENHARIA QUIMICA::PROCESSOS INDUSTRIAIS DE ENGENHARIA QUIMICA